Using Learning Analytics to Monitor and Enhance Early Reading Fluency: A Study in Brazilian Public Schools - Silva, Thomaz Edson Veloso da; Guerino, Guilherme Corredato; Rodrigues, Luiz (Anais do Workshop de Aplicações Práticas de Learning Analytics e Inteligência Artificial no Brasil (WAPLA), 2025)
This paper examines the use of Learning Analytics (LA) to monitor and improve early reading fluency in Brazilian public schools. In July 2024, the Chapecó city launched a policy for assessing 2,072 second-grade students over six monthly cycles using three distinct instruments. Students were classified into six fluency categories, enabling targeted interventions. Results showed a substantial reduction in the number of Non-readers and a significant increase in Fluent Readers across six applications. These findings suggest that systematic application of LA tools, combined with regular teacher feedback and datainformed instructional adjustments, can produce measurable improvements in early literacy outcomes, offering insights for policymakers and educators seeking to implement data-informed strategies in early reading programs.